Pengaruh Kepuasan Pelanggan dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Dimediasi oleh Nilai Layanaan yang Dirasakan, Citra Perusahaan, dan Reputasi Perusahaan - Aldara Syafa'a Maristha; Soepatini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the effect of customer satisfaction and service quality on customer loyalty in GO-JEK, mediated by perceived value, corporate image, and corporate reputation. The sample consists of 150 respondents aged over 17 years and Gojek users. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3. The results show that customer satisfaction, service quality, corporate image, and corporate reputation positively affect Gojek customers' perceived value. Corporate image also directly influences customer loyalty, while corporate reputation is not significant. Perceived value enhances customer loyalty. Service quality and corporate image act as mediators in this relationship, whereas customer satisfaction and corporate reputation do not mediate the effect.